Church Dogmatics by Karl Barth - Deegan, Daniel L. (Scottish journal of theology, 1962)
In this third part of volume III of his Dogmatics Barth sets forth the doctrine of divine providence as the objective and universal rule of God which establishes and encompasses but does not absorb the existence of the person or community which becomes the object of His preservation. Barth's steadfast aim has been to produce a theology dominated by its object, Jesus Christ. This part of the Dogmatics is no exception, for here he argues that the order of being and the order of knowledge start with the event of God's action in Christ. Hence he does not speak of a natural theology with an independent cosmological interest in the work of divine preservation, for he insists that Scripture is differently orientated. It does not witness simply to the highest being as first cause; it witnesses primarily to the Lord of history, the God of the Covenant. This means that the doctrine of providence does not become a Weltanschauung. What Barth says concerning this problem in C.D.III.3 should be read in conjunction with C.D.III.2, pp. 3ff. Because he affirms that the central concern of theology is the relation of God and man established in Jesus Christ he regards cosmology as a peripheral concern arid draws the line against attempts to integrate scientific views and theological interpretation into a comprehensive Weltanschauung. Yet he readily admits that the natural sciences which know their limits have their appropriate place in elucidating the nature of man against the background of creation.